Physical vapor deposition technology for coated cutting tools: A review. Issue 11 (1st August 2020) - Deng, Yang; Chen, Wanglin; Li, Bingxin; Wang, Chengyong; Kuang, Tongchun; Li, Yanqiu
Abstract: Due to various difficult-to-machine materials and increasingly severe machining conditions, more and more attention has been paid to the physical vapor deposition (PVD) technology in recent decades to deposit hard coatings on cutting tools. Combined with the status of industrial application of PVD technology, this paper reviews the main PVD techniques for coated cutting tools from the perspective of the overall PVD coating equipment, including cathodic arc evaporation and magnetron sputtering as well as their hybrid techniques, and the plasma etching which is critical for coating adhesion strength is also involved. With regard to hard coating deposition on cutting tools, the basic principle, cathode configuration, magnetron and power supply are outlined. Issues related to target ionization ratio, coating deposition rate, coating properties and industrial application of numerous PVD techniques are also highlighted. On plasma etching, inert gas ion etching and metal ions etching are discussed. Finally, this paper summarizes and prospects the PVD technology used for coated cutting tools.